Pengaruh Struktur Modal, Kepemilikan Manajerial dan Ukuran Perusahaan terhadap Nilai Perusahaan pada Perusahaan Sub Sektor Software & IT Service yang Terdaftar di BEI - Ni Komang Ririn Wulandari; Gede Putu Agus Jana Susila (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to examine the effect of capital structure, managerial ownership and company size on company value. The subjects of this study are software & IT service sub-sector companies listed on the Indonesia Stock Exchange and the objects of this study are capital structure, managerial ownership, company size and company value. This study uses purposive sampling in determining the sample and the number of samples is 29 companies. The design of this study is quantitative causal and the data in the study are secondary data sourced from the company's annual report taken from the IDX and analyzed using multiple linear regression analysis methods with the help of SPSS in data processing. The results of the study show (1) Capital structure, managerial ownership and company size simultaneously have a significant effect on company value. (2) Capital structure has a positive and insignificant effect on company value. (3) Managerial ownership has a negative and insignificant effect on company value. (4) Company size has a positive and significant effect on company value.